Case Technology in Teaching Professional Foreign Communication to Law Students: Comparative Analysis of Distance and Face-to-Face Learning - Oksana Sheredekina; Irina Karpovich; Larisa Voronova; Tatyana Krepkaia (MDPI AG, 2022)
Foreign language speaking skills need much practice in order to be improved, which is why it is essential to use different teaching techniques to instruct students effectively. The multiplicity and multitasking of the foreign language teaching process requires the introduction of technology that ensures consistently effective results of professional foreign language learning, i.e., case technology in the algorithmized educational process. The conducted research contributes to the issue of case technology implementation-the algorithm of professional task solutions, aimed at improving students' English-speaking skills-in teaching professional legal English. The aim of the study is to investigate the effectiveness of case technology in the improvement of ESP speaking skills in the course of distance and face-to-face learning. Comparative analysis of the distance and face-to-face format of case technology implementation in teaching professional foreign communication to law students was carried out in the course of the two-semester study conducted at SPbPU (N 120) in the period from January 2020 to July 2021. Mixed qualitative and quantitative methods were applied to collect and analyse data for the study. The results of the study showed that, for such assessment criteria as task completion, discourse competence and meaningfulness, the use of case technology in a face-to-face format was more effective than the one carried out on-line. As it can have some pedagogical implications on the improvement of English-speaking skills while teaching professional legal English at university, additional effort should be taken to ensure the effectiveness of case technology in the course of distance learning.